Demanda interna de alimentos balanceados para consumo animal como factor del incremento en las importaciones de maíz amarillo en Colombia entre 2015-2019 (2023)
he main objetive of this research is identify those factors that directly affect the growth of imports, considering that balanced feeds, are associated with the demand for yellow corn and the national production of this cereal. Continuing with this, it will be necessary to interpret data to finally verify the factors that influence the increase in imports of yellow corn in Colombia. In this way, an econometric model was carried out considering imports of yellow corn as the dependent variable and the demand for balanced foods and the production of yellow corn as independent variables. Also, a multiple linear regression model was performed, evidencing that yellow corn imports, feed demand and yellow corn production demonstrate a statistically significant relationship in the 2015-2021 time periods.